Bioremediation of Hexavalent Chromium By Bacteria Isolated From Buriganga River, Dhaka City - Osail, SM; Sanny, SI; Kabir, MS (Stamford Journal of Microbiology, 2023)
Environmental pollution due to hexavalent chromium (Cr6+) is widespread because of the anthropogenic activities in various industrial processes, notably in leather tanning. Hexavalent chromium (Cr6+) is considered as highly toxic, carcinogenic, and mutagenic due to its high solubility in water, interaction with cellular proteins, and biological membrane permeability. Trivalent chromium (Cr3+), on the other hand, is less water-soluble, and relatively benign in nature. Thus, bioreduction of toxic Cr6+ to relatively non-toxic Cr3+ by microorganisms can be an inexpensive and eco-friendly option for chromium bioremediation. In this regard, the present study attempted to isolate chromium-reducing bacteria from Buriganga River in order to assess their capability for chromium bioremediation. Ten chromium-tolerating bacterial isolates were successfully identified. The results revealed that these isolates, particularly strains of Bacillus subtilis, exhibited a remarkable ability to remove up to 89% of hexavalent chromium from the contaminated medium within three days of incubation. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 25-29